Многомерные модели бегущих волн и нелинейных форм колебаний в цилиндрических оболочках - Аврамов, К.В. (Прикладная механика, 2011)
A model is proposed for nonlinear dynamical deformation of cylindrical shell, which takes into account a few united modes. Two regimes of motions are considered in the model – the regime of running waves and the regime of nonlinear normal modes.